European powers policy towards Turkey in the years 1903-1914 - Rubacha, Jarosław (Balcanica Posnaniensia. Acta et studia, 2014)
The years 1903-1914 should be considered as the most interesting period in the activity of the great powers states in South-East Europe and Near East for a few reasons discussed below. In the final period of the formation of the antagonistic military-political alliances in Europe, the so called “Concert of Europe” mainly showed a great interest in maintaining the status quo and preventing any conflicts which could occupy their attention. These states also focused on Turkey and especially on its European dominion. As a result, they jointly conducted reforms in Macedonia or tried to prevent the outbreak of war between the High Porte and the Balkan allies in 1912. At the same time, the powers did not stop their endeavors to realize their own political or economic aims at the cost of Turkey (e.g. the annexation of Bosnia and Herzegovina by Austro-Hungary in 1908, the occupation of Tripolitania and Cyrenaica by Italy in 1911). Their aim was to eliminate the influences and block the initiative of their competitors.